2016
DOI: 10.1386/fspc.3.2.251_1
|View full text |Cite
|
Sign up to set email alerts
|

Fashion brands and gay/lesbian-inclusive advertising in the USA

Abstract: Within the United States general attitudes towards gays and lesbians (GL) are rapidly undergoing change. Several researchers have previously documented that heterosexual consumers respond negatively to advertisements featuring same-sex couples. At this critical juncture, it is important to reexamine consumer response to fashion advertisements featuring GL images. Using a small qualitative study (n = 10) and an experiment (n = 202) our research purpose was to determine whether consumer attitude towards advertis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous studies [3,9] have shown that moderate exposure of sexual minorities can lead to higher levels of empathy and social connection as long as this process is subtle and continual.…”
Section: The Insertion Of Gay-friendly In the Spot As A Determinant O...mentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies [3,9] have shown that moderate exposure of sexual minorities can lead to higher levels of empathy and social connection as long as this process is subtle and continual.…”
Section: The Insertion Of Gay-friendly In the Spot As A Determinant O...mentioning
confidence: 97%
“…Sixteen participants claim that brands such as Movistar acknowledge that their audiences appreciate added value, position on an issue, problem, and social contribution, which adds points in favor of the brand. Previous findings [2,9,10] have shown that consumers do not want materialistic brands, but rather brands which are socially responsible, and that as a result, brands obtain the benefits of loyalty, trust and retention from their customers [1,11]. Four participants questioned Movistar's social background, and due to the continuity of the topic, the use of exaggerated homosexual representation, the broadcasting schedule, and the poor service, they would reconsider leaving the brand.…”
Section: The Insertion Of Gay-friendly In the Spot As A Determinant O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, consumers can use brands to form their self-concept (Akermanidis & Venter, 2014). Several works evidence the contribution that can be made by advertising imagery to individuals' sexual identity (Chae et al, 2016;Gong, 2020;Holz Ivory, 2019;Mikkonen, 2010;Oakenfull et al, 2008). As result of this, the use of gay men and lesbians' subculture symbols in advertising, that reflect gay/lesbian identity, for instance referencing clothes, language, lifestyle etc, have meaning for the community and generate empathy with them (Oakenfull et al, 2008).…”
Section: Consumers' Self-concepts and Brandsmentioning
confidence: 99%